2010
DOI: 10.1093/geronb/gbq039
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Neighborhood Density Effects on Spoken Word Recognition and Production in Healthy Aging

Abstract: We examined the effects of lexical competition and word frequency on spoken word recognition and production in healthy aging. Older (n = 16) and younger adults (n = 21) heard and repeated meaningful English sentences presented in the presence of multitalker babble at two signal-to-noise ratios, +10 and -3 dB. Each sentence contained three keywords of high or low word frequency and phonological neighborhood density (ND). Both participant groups responded less accurately to high- than low-ND stimuli; response la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
86
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 32 publications
13
86
1
2
Order By: Relevance
“…Most importantly, individual inhibitory abilities were found to be correlated with lexical identification performance on words with many neighbors in a study with young and older adults (and not with performance on the "easy" words with few neighbors), again suggesting that inhibitory abilities play a role in the auditory recognition of words with many similar-sounding neighbors (Sommers & Danielson, 1999). Consistent with these results, Taler, Aaron, Steinmetz, and Pisoni (2010) found that poorer inhibitory function (as indexed by performance on a Stroop paradigm) is associated with a greater difference between performance on high vs. low neighborhood density words at poor signal-to-noise ratios. Note that this relationship between inhibitory function and lexical recognition exists even though the type of inhibition assessed in a Stroop task is under the participant's control to a greater extent than is inhibition in the word recognition system.…”
Section: Introductionmentioning
confidence: 62%
“…Most importantly, individual inhibitory abilities were found to be correlated with lexical identification performance on words with many neighbors in a study with young and older adults (and not with performance on the "easy" words with few neighbors), again suggesting that inhibitory abilities play a role in the auditory recognition of words with many similar-sounding neighbors (Sommers & Danielson, 1999). Consistent with these results, Taler, Aaron, Steinmetz, and Pisoni (2010) found that poorer inhibitory function (as indexed by performance on a Stroop paradigm) is associated with a greater difference between performance on high vs. low neighborhood density words at poor signal-to-noise ratios. Note that this relationship between inhibitory function and lexical recognition exists even though the type of inhibition assessed in a Stroop task is under the participant's control to a greater extent than is inhibition in the word recognition system.…”
Section: Introductionmentioning
confidence: 62%
“…The idea was that the impact of PhND changes with vocabulary growth during development. Further studies reported an inhibitory effect of PhND in English speech production latencies (Luce & Pisoni, 1998;Munson et al, 2005;Taler et al, 2010;Vitevitch & Luce, 1998). In these studies, participants were asked to repeat as fast as possible a word or sentence presented acoustically (i.e., shadowing task).…”
Section: Are There Cross-linguistic Differences In the Direction Of Tmentioning
confidence: 99%
“…The shadowing task involves both speech perception and speech production, and hence may reflect contributions of either process (Bates & Liu, 1996). For example, shadowing experiments are used to investigate the relationship between input and output phonological representations (e.g., Mitterer & Ernestus, 2008;Taler et al, 2010). Therefore, the inhibitory effect may stem in part from production processes, yet attributing the results from shadowing studies to perception versus production processes should be done cautiously.…”
Section: Are There Cross-linguistic Differences In the Direction Of Tmentioning
confidence: 99%
“…In addition, the effect of neighborhood density may vary across different levels of noise. Taler, Aaron, Steinmetz, and Pisoni (2010) found that the neighborhood density effect on recognition was larger in a challenging listening condition (−3-dB signal-to-noise ratio [SNR]) than in a favorable listening condition (+10-dB SNR). This result implies that noise may amplify the effect of neighborhood density because adults show greater reliance on top-down processing when the listening condition worsens.…”
Section: Effect Of Noise On Word Learningmentioning
confidence: 99%